2019
DOI: 10.1186/s12886-019-1059-4
|View full text |Cite
|
Sign up to set email alerts
|

Ocular toxicity of intravitreal melphalan for retinoblastoma in Chinese patients

Abstract: Background To evaluate the efficacy, complications, and clinical characteristics, including the ocular toxicity, of intravitreal melphalan(IVM) treatment for vitreous seeding in Chinese retinoblastoma patients. Methods This was a retrospective, non-comparative analysis including 30 consecutive eyes of 23 patients with viable persistent or recurrent vitreous seeding following retinoblastoma treatment. All of the eyes received IVM injections (20–33 μg). Vitreous seeding c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…The findings observed using different concentrations of Melphalan point to potential toxicity causing thrombo-hemorrhagic changes when used in higher doses. Despite the conjectural nature of this finding, it correlates to clinical outcomes reported of vascular occlusion and vitreous hemorrhage following intravitreal Melphalan in eyes with RB [ 12 ].…”
Section: Discussionsupporting
confidence: 68%
“…The findings observed using different concentrations of Melphalan point to potential toxicity causing thrombo-hemorrhagic changes when used in higher doses. Despite the conjectural nature of this finding, it correlates to clinical outcomes reported of vascular occlusion and vitreous hemorrhage following intravitreal Melphalan in eyes with RB [ 12 ].…”
Section: Discussionsupporting
confidence: 68%
“…Based on another theory [ 20 ] that darkly pigmented eyes are more vulnerable to intraocular inflammation. Xue et al also postulated that intravitreal melphalan in the Asian population might incite inflammation more than that of the Caucasian population [ 21 ]. Some studies support the use of topotecan in such eyes as it is thought to induce lesser inflammation [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…While singular IVM dosages higher than 30 µg may increase the risk of toxicity, neither the cumulative dosage nor the number of injections that an eye received correlates with toxicity grade [17]. It has also been previously suggested that more deeply pigmented eyes may be at increased risk for toxicity due to increased absorption of melphalan by the choroid and retinal pigment epithelium [7,11,24,25]. Regardless, not all deeply pigmented eyes experience IVM toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Although severe toxicity was initially thought to be associated with posterior vitreous detachment, thus concentrating the chemotherapy to the retina, a review of a larger cohort of patients failed to find an association between posterior vitreous detachment and toxicity [10]. A recent publication from a Chinese cohort described significant toxicity: 40% of patients with grade 3 or higher toxicity, 40% with vascular occlusion (similar to the acute hemorrhagic presentation), 40% anterior toxicity, and upwards of 20% with optic atrophy [11].…”
Section: Introductionmentioning
confidence: 99%